UBA-аналіз як засіб підвищення інформаційної безпеки автоматизованих систем - Грицаненко, Я. Ю. (ХНУРЕ, 2023)
The principles of UBA-analytics operation are considered, as well as tasks that UBA-systems should solve to ensure information security in automated of military automated systems.
Keywords: UBA-аналіз